Value chain finance: Beyond microfinance for rural entrepreneurs - Royal Tropical Institute; International Institute of Rural Reconstruction (Royal Tropical Institute, 2012)
The authors of this book – the book’s ‘heroes’ – are the practitioners themselves, people and financial institutions who are developing tools to provide small enterprises with the capital they need. Here they tell their stories, exploring the novel ways they have found to provide financial services. Clearly explained with the use of diagrams, tables and figures, readers can find out all they need to know to increase profits throughout the value chain and so improve the lives of the rural poor.